The golden genome annotation of Ganoderma lingzhi reveals a more complex scenario of eukaryotic gene structure and transcription activity - Lining Wang; Peiqi Shi; Zhaohua Ping; Qinghua Huang; Liqun Jiang; Nianfang Ma; Qingfu Wang; Jiang Xu; Yajie Zou; Zhihai Huang (BMC Biology)
Abstract Background It is generally accepted that nuclear genes in eukaryotes are located independently on chromosomes and expressed in a monocistronic manner. However, accumulating evidence suggests a more complex landscape of gene structure and transcription. Ganoderma lingzhi, a model medicinal fungus, currently lacks high-quality genome annotation, hindering genetic studies. Results Here, we reported a golden annotation of G. lingzhi, featuring 14,147 high-confidence genes derived from extensive manual corrections. Novel characteristics of gene structure and transcription were identified accordingly. Notably, non-canonical splicing sites accounted for 1.99% of the whole genome, with the predominant types being GC-AG (1.85%), GT-AC (0.05%), and GT-GG (0.04%). 1165 pairs of genes were found to have overlapped transcribed regions, and 92.19% of which showed opposite directions of gene transcription. A total of 5,412,158 genetic variations were identified among 13 G. lingzhi strains, and the manually corrected gene sets resulted in enhanced functional annotation of these variations. More than 60% of G. lingzhi genes were alternatively spliced. In addition, we found that two or more protein-coding genes (PCGs) can be transcribed into a single RNA molecule, referred to as polycistronic genes. In total, 1272 polycistronic genes associated with 2815 PCGs were identified. Conclusions The widespread presence of polycistronic genes in G. lingzhi strongly complements the theory that polycistron is also present in eukaryotic genomes. The extraordinary gene structure and transcriptional activity uncovered through this golden annotation provide implications for the study of genes, genomes, and related studies in G. lingzhi and other eukaryotes.